A record of Holocene climate changes in central Asia derived from diatom-inferred water-level variations in Lake Kalakuli (Eastern Pamirs, western China) - Peng, Yumei; Rioual, Patrick; Jin, Zhangdong (Frontiers in Earth Science, 2022)
The unique geographical and climatic settings of the eastern Pamirs make this region sensitive to the Westerlies and global climate change. Holocene fluctuations in water-level of Lake Kalakuli, a proglacial lake located to the northwest of the Muztag Ata glacier, were reconstructed based on diatoms from a ~15 m long sediment core spanning the last ~9900 years. To establish how diatom species distribute in relation to water depth in Lake Kalakuli, a dataset of 45 surface sediment samples was retrieved from different water depth. Statistical analyses such as cluster analysis (TWINSPAN) and redundancy analysis (RDA) were used to demonstrate that the water depth gradient is the main environmental gradient driving the distribution of these diatom assemblages. A diatom-water depth transfer function, was then developed using a WAPLS component 2 model (R2=0.89, RMSEP=1.85 m) and applied to the Holocene diatom sequence from Lake Kalakuli. Due to the large residual errors in the model only the general trends in water level are proposed. Effective moisture increased rapidly during the early Holocene, as the water depth reached a high level from the lowest level within about two thousand years. Only small amplitude fluctuations were recorded during the mid- and late Holocene until the last few hundred years when a marked increase occurred. Changes in summer insolation over the northern hemisphere drove the advances and retreats of the Muztag Ata glacier, which in turn controlled the fluctuations of water level in this lake. The diatom-derived paleoclimatic trend from Lake Kalakuli is consistent with the Holocene climate evolution in the Westerlies-dominated area of Central Asia.